2010
DOI: 10.1038/bmt.2010.87
|View full text |Cite
|
Sign up to set email alerts
|

Co-infusion of ex vivo-expanded, parental MSCs prevents life-threatening acute GVHD, but does not reduce the risk of graft failure in pediatric patients undergoing allogeneic umbilical cord blood transplantation

Abstract: When compared with BMT, umbilical cord blood transplantation (UCBT) is associated with a lower rate of engraftment and delayed hematological/immunological recovery. This leads to increased risk of TRM in the early post transplantation period due to infection. Acute GVHD, although occurring less frequently in UCBT compared with BMT, is also significantly associated with increased rate of early TRM. BM MSCs are known to support normal in vivo hematopoiesis, and co-transplantation of MSCs has been shown to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 50 publications
2
121
0
4
Order By: Relevance
“…48 The results are more promising when used at an early stage of GVHD. 86 Bernardo et al 96 treated grade-II acute GVHD with MSCs and reported no deaths that were attributable to acute GVHD as compared with 26% in retrospective control patients. According to animal data, not only early treatment, but also repeated doses may be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The results are more promising when used at an early stage of GVHD. 86 Bernardo et al 96 treated grade-II acute GVHD with MSCs and reported no deaths that were attributable to acute GVHD as compared with 26% in retrospective control patients. According to animal data, not only early treatment, but also repeated doses may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…No acute side effects were seen after infusion of MSC doses at a range of 1-5 Â 10 6 cells/kg in 46 HLA-identical sibling transplant recipients. Bernardo et al 96 used MSCs at the time of HSCT transplantation in children who were recipients of cord blood grafts. Ball et al 97 performed co-transplantation of MSCs in children undergoing haploidentical HSCT.…”
Section: Stromal Cells For Prevention Of Gvhdmentioning
confidence: 99%
“…50 In another pediatric, phase I/II clinical study, the safety and efficacy of co-transplantation of parental MSCs was tested in 13 pediatric patients given UCB-derived HCs; the results were compared with those obtained in historical controls receiving UCBT alone. 16 The feasibility and safety of the approach was confirmed; however, in contrast with pre-clinical results 36 and the experience reported in the haploidentical transplants, 15 no difference was found in terms of both engraftment rate and speed of hematological recovery between the two groups, although much less study patients were given G-CSF as compared with controls. Interestingly, MSC co-infusion significantly reduced the incidence of life-threatening acute GvHD and GvHD-associated TRM, as compared with controls.…”
Section: Clinical Trials Of Msc Infusion To Promote Engraftmentmentioning
confidence: 41%
“…Interestingly, MSC co-infusion significantly reduced the incidence of life-threatening acute GvHD and GvHD-associated TRM, as compared with controls. 16 In adult patients receiving UCBT with coinfusion of third-party donor-mobilized HCs, MSC administration at the time of transplantation had no effect on the kinetics of UCB cell engraftment, as well as on GvHD prevention. 51 Altogether, these data indicate that co-transplantation of HCs and MSCs is safe, while there is still uncertainty about a real efficacy of MSCs on promoting engraftment of donor cells and accelerating the speed of hematological recovery.…”
Section: Clinical Trials Of Msc Infusion To Promote Engraftmentmentioning
confidence: 99%
See 1 more Smart Citation